(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Sgadova V. V. The content of future lecturer psychology-pedagogical preparation to professional creative activity. The content of psychology-pedagogical preparation of future lecturers to professional creative activity is analyzed. Different forms of students’ educational activity which develop their creative skills are highlighted.